2005
DOI: 10.1007/s11095-005-2493-y
|View full text |Cite
|
Sign up to set email alerts
|

A Population Pharmacokinetic Model for Montelukast Disposition in Adults and Children

Abstract: The model developed can adequately describe the intravenous pharmacokinetics of montelukast and can be used as a useful tool for dose selection in pediatric subpopulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The PK of montelukast in this study was found to be consistent with a 1st-order absorption and 1-compartment elimination model with CL/F and V/F increasing with body weight and a proportional error structure. These results were similar to those from a previous study [ 20 ] and a previous PPK analysis in non-Japanese paediatric patients. [ 17 ] We observed that montelukast plasma concentrations decreased slightly with age and that the relationship between PK and age is likely explained by the underlying relationship between age and body weight.…”
Section: Discussionsupporting
confidence: 92%
“…The PK of montelukast in this study was found to be consistent with a 1st-order absorption and 1-compartment elimination model with CL/F and V/F increasing with body weight and a proportional error structure. These results were similar to those from a previous study [ 20 ] and a previous PPK analysis in non-Japanese paediatric patients. [ 17 ] We observed that montelukast plasma concentrations decreased slightly with age and that the relationship between PK and age is likely explained by the underlying relationship between age and body weight.…”
Section: Discussionsupporting
confidence: 92%
“…Like oxycodone, milrinone, and voriconazole, midazolam is hepatically metabolized, and the model of midazolam pharmacokinetics in children showed that age was not an important covariate compared to weight. Ramakrishnan et al 26 studied intravenous montelukast in children with asthma and identified total body water as more predictive than weight and both more predictive than age. Taken together, these are interesting findings because the known developmental regulation of the cytochrome C P450 (CYP) system elucidated by de Wildt et al 27 would predict an increasing CL with increasing age in the ages under study.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of weight on montelukast clearance is in agreement with the results of a previous pharmacokinetic study in children. 23 The clearance of montelukast increased allometrically along with body weight.…”
Section: Discussionmentioning
confidence: 99%
“…An external validation of the previously published model in children was performed at the first step; then, the validated model was used to derive individual clearance of montelukast for the following pharmacogenetic analysis. A linear threecompartment pharmacokinetic model 23 with 73% bioavailability of the chewable tablets 7 and a constant absorption rate (Ka) of 0.5L/h 24 was evaluated. The following modeling information was extracted from the published article: interindividual variability for clearance (CL), central compartment volume of distribution (Vc) and peripheral volume of distribution (Vp) (% coefficient of variation [%CV], 24.2%, 14.0% and 45.4%, respectively) by exponential error model, residual variability using a combined additive and proportional model (%CV, 3.7 ng/mL and 10.4%) and a significant influence of current weight (CW) on CL and V c , V P1 , V P2 , Q 1 , Q 2 with the following regression equations (equations 1-6):…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%